Online Contents / Gemeinsamer Bibliotheksverbund - Gemeinsamer Bibliotheksverbund (1993)
The database Online Contents - SSG East and Southeast Asia provides access to articles from over 255 periodicals beginning with the year of publication 1993 in the field of East Asian studiesis a selection of bibliographic data from the Swets database Online Contents which is supplemented weekly by additional data provided by a number of German libraries.